Polymer, super-hydrophobic coating and preparation method thereof
By introducing DHPMT derived structure and long-chain alkyl side chains into the polymer, the polymers used to prepare superhydrophobic coatings are synthesized, which solves the problem of insufficient bonding of superhydrophobic coatings in the prior art, and achieves efficient oil-water separation and coating performance improvement.
Patent Information
- Application Number
- CN202311115183.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-31
AI Technical Summary
There is still room for improvement in the superhydrophobic coatings in the prior art in terms of bonding firmness, tolerance and durability to the substrate.
The polymer with the main chain containing DHPMT derived structure and the side chain containing long-chain alkyl groups is used, and the polymer is synthesized by the addition reaction of DHPMT with acrylate and substitution reaction with halogenated hydrocarbons, and then the superhydrophobic coating is prepared, and the copper mesh is modified by dip coating method to construct a superhydrophobic filter mesh on the surface.
The excellent bonding firmness, solvent resistance and durability of the coating is achieved, and the superhydrophobicity, tolerance and durability of the superhydrophobic copper mesh is improved, and it is suitable for efficient separation of a variety of oil and water mixtures.
Smart Images

Figure CN119529274A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polymer, a super-hydrophobic coating and a preparation method thereof, and belongs to the field of polymer chemistry. Background Art
[0002] With the development of living and production standards, traditional polymers can no longer meet application needs, and the development of polymers with new structures and new functions has become an important topic of concern in the field of polymer chemistry. 3,4-Dihydropyrimidine-2-thione (DHPMT) can be synthesized in one step through a three-component Biginelli reaction. It is a functional heterocycle that has shown good biological activity in antagonizing calcium ion channels, antibacterial, anticancer, and antioxidant properties. Not only that, the DHPMT structure also has high reactivity similar to thiourea, and can be efficiently and continuously post-modified, so that a variety of functional structures can be easily introduced into the molecular structure, giving the molecule rich functions. Therefore, polymers with DHPMT (derivative) structures have potential application value in many fields, and the development of new polymers containing DHPMT (derivative) structures and corresponding synthesis methods is of great significance.
[0003] For example, in Non-Patent Document 1, a polymer having a DHPMT structure in the main chain or the side chain is synthesized and chemically modified by an acrylate-DHPMT addition reaction, thereby greatly improving the solubility of the polymer in water.
[0004] Super-hydrophobic surface has excellent properties such as anti-sticking, anti-fouling, anti-icing, self-cleaning, etc., and has important applications in the fields of aerospace, construction industry, and electronics industry. Modifying the surface of materials with super-hydrophobic coatings is one of the important ways to achieve super-hydrophobicity of materials. However, since super-hydrophobic coatings have very low surface energy, the combination of coatings and substrates is often not strong, resulting in the coating's environmental tolerance and durability being weak.
[0005] In this regard, some efforts have been made in the prior art. For example, Patent Document 1 discloses a highly weather-resistant super-hydrophobic polymer and a coating composition comprising the same, which enables the highly weather-resistant super-hydrophobic polymer to contain a specific super-hydrophobic segment, a compatibility regulating segment and a capping segment, thereby achieving super-hydrophobic properties while achieving excellent weather resistance and good compatibility, thereby giving the coating a long-lasting super-hydrophobic effect.
[0006] References:
[0007] Non-patent literature 1: Polym.Chem., 2022, 13, 6322
[0008] Patent document 1: CN116217935A Summary of the invention
[0009] Problem that the invention aims to solve
[0010] The super hydrophobic coating in the prior art still has a lot of room for improvement in terms of bonding firmness, tolerance and durability with a substrate. The object of the present invention is to provide a polymer capable of imparting excellent bonding firmness, tolerance and durability to a coating, a method for preparing the polymer, and a super hydrophobic coating composition comprising the polymer.
[0011] Solutions for solving problems
[0012] In view of the above problems, the inventors have conducted long-term and in-depth research and proposed a polymer whose main chain contains a DHPMT derivative structure and whose side chain contains a long-chain alkyl group. It is also proposed that a precursor polymer is first synthesized by an addition reaction of DHPMT and acrylate, and then the precursor polymer is post-modified by a substitution reaction of DHPMT and halogenated hydrocarbons to obtain the polymer, and then the polymer is used to prepare a super-hydrophobic coating, and a copper mesh is modified by a dip coating method to construct a filter mesh with a super-hydrophobic surface.
[0013] Specifically, the present invention solves the problem of the present invention through the following solutions.
[0014] [1] A polymer comprising a repeating unit represented by the following formula (1):
[0015]
[0016] in,
[0017] R1 and R2 are identical or different and represent an alkylene group having 1 to 30 carbon atoms, wherein one or more non-adjacent -CH2- groups are optionally replaced by -O-, -S-, -CO-, -NR- or -CH2- in such a way that the O and / or S atoms are not directly connected to each other. 0 -, -C(=O)NH-, -C(=O)O-, -OC(=O)-, -C=C-, and wherein one or more hydrogen atoms are optionally substituted by halogen;
[0018] Ar represents a phenylene group, which is optionally substituted mono- or poly-substituted by an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, or a halogen group;
[0019] R3 and R4 are the same or different and represent an alkyl group having 5 to 50 carbon atoms, wherein the alkyl group is optionally substituted with fluorine or polysubstituted with fluorine;
[0020] * indicates the attachment site.
[0021] [2] The polymer according to [1], wherein in formula (1), R1 represents a group -OZO-, wherein Z represents an alkylene group having 1 to 20 carbon atoms, wherein one or more non-adjacent -CH2- groups in the alkylene group are optionally replaced by -O-, -S-, -CO-, -C(=O)O-, -OC(=O)- in a manner that the O and / or S atoms are not directly connected to each other, and wherein one or more hydrogen atoms are optionally replaced by halogen; R2 represents an alkylene group having 2 to 20 carbon atoms, wherein one or more non-adjacent -CH2- The group is optionally replaced by -O-, -S-, -CO-, -C(=O)O-, -OC(=O)- in a manner that the O and / or S atoms are not directly connected to each other, and one or more hydrogen atoms are optionally substituted by halogen; Ar represents a phenylene group, which is optionally mono- or poly-substituted by an alkyl group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, or a halogen; R3 represents an alkyl group having 5 to 20 carbon atoms, which is poly-substituted by fluorine; R4 represents an alkyl group having 12 to 30 carbon atoms, which is optionally mono- or poly-substituted by fluorine.
[0022] [3] The polymer according to [2], wherein Z represents an alkylene group having 4 to 12 carbon atoms; R2 represents an alkylene group having 4 to 12 carbon atoms; Ar represents a phenylene group, which is optionally mono- or poly-substituted by an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, or a halogen group; R3 represents an alkyl group having 6 to 16 carbon atoms, which is optionally mono- or poly-substituted by fluorine; and R4 represents an alkyl group having 15 to 25 carbon atoms, which is optionally mono- or poly-substituted by fluorine.
[0023] [4] The method for producing a polymer according to any one of [1] to [3], comprising the following steps:
[0024] Step a): reacting the compound represented by formula (2) and the compound represented by formula (3) with thiourea to obtain a monomer B represented by formula (4);
[0025]
[0026] Step b): subjecting the monomer A represented by formula (5) to addition polymerization with the monomer B to obtain a precursor polymer represented by formula (6);
[0027]
[0028] Step c): subjecting the precursor polymer represented by formula (6) to a substitution reaction with the compound represented by formula (7) to obtain the polymer;
[0029] R3-I Formula (7)
[0030] Wherein, each group in formula (2) to formula (7) has the definition given in any one of claims 1 to 3; n represents the number of repeating units in the precursor polymer, which is an integer of 1 to 50.
[0031] [5] The preparation method according to [4], wherein
[0032] The reaction in step a) is carried out in a solvent in the presence of a catalyst, wherein the catalyst is one or more selected from Bronsted acid and Lewis acid, preferably one or more selected from magnesium chloride, p-toluenesulfonic acid, hydrochloric acid, zinc chloride, ammonium cerium nitrate, ytterbium trifluoromethanesulfonate, and trimethylsilyl chloride; the solvent is a polar solvent, preferably one or more selected from acetic acid, N,N-dimethylformamide, methanol, ethanol, and acetonitrile; in terms of moles, the compound represented by formula (2): the compound represented by formula (3): thiourea = 1: (1.8-2.2): (2.5-3.5); the reaction temperature is 25-100°C; the reaction time is 2-24 hours;
[0033] The addition polymerization reaction in step b) is carried out in a solvent in the presence of a catalyst, wherein the catalyst is a base, and the base is preferably an inorganic base, and more preferably one or more selected from sodium carbonate, potassium carbonate, potassium hydroxide, and sodium hydroxide; the solvent is a polar aprotic solvent; in terms of moles, monomer A:monomer B:catalyst=1:(0.9-1.1):(0.05-0.20); the reaction temperature is 80-120°C; and the reaction time is 4-12 hours;
[0034] The substitution reaction in step c) is carried out under the catalysis of a base and an iodine salt, wherein the base is preferably an inorganic base, more preferably potassium carbonate and / or sodium carbonate; the iodine salt is preferably sodium iodide and / or potassium iodide; in terms of moles, the precursor polymer: the compound represented by formula (7): the base: the iodine salt = 1: (3.5-4.5): (2.5-4.5): (0.05-0.5); the reaction temperature is 80-120° C.; and the reaction time is 12-36 hours.
[0035] [6] A super hydrophobic coating comprising the polymer according to any one of [1] to [3] and a solvent.
[0036] [7] A super hydrophobic coating comprising the polymer according to any one of [1] to [3].
[0037] [8] A super-hydrophobic copper mesh, comprising a copper mesh substrate and a polymer layer located on a surface of the copper mesh substrate, wherein the polymer layer comprises the polymer according to any one of [1] to [3].
[0038] [9] The method for preparing a super-hydrophobic copper mesh according to any one of [8], comprising the following steps:
[0039] The super hydrophobic coating described in [6] is applied to the surface of the copper mesh substrate and optionally dried.
[0040]
[10] Use of the super hydrophobic copper mesh described in [8] for oil-water separation.
[0041] Effects of the Invention
[0042] The polymers of the present invention can impart excellent substrate bonding, solvent resistance and durability to the coating.
[0043] The raw materials used in the preparation method of the polymer of the present invention are cheap and easily available, the reaction conditions are simple, the reaction speed is fast and the efficiency is high.
[0044] The super-hydrophobic coating of the present invention can obtain a super-hydrophobic coating with excellent bonding firmness with a substrate, tolerance and durability.
[0045] The super-hydrophobic copper mesh of the present invention has excellent super-hydrophobicity, tolerance and durability, can be used for separation of various oil-water mixtures, and has large separation flux and high separation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 a) is a synthetic route diagram of polymer P2 in Example 1;
[0047] Figure 1 b) is the precursor polymer P1 in Example 1 1 H NMR spectrum;
[0048] Figure 1 c) is the polymer P2 in Example 1 1 H NMR spectrum;
[0049] Figure 2 a) is the contact angle test result of the copper mesh in Example 2 before and after the surface is modified with a super-hydrophobic coating;
[0050] Figure 2 b) is a scanning electron microscope photograph of the copper mesh in Example 2 before and after the surface is modified with a super-hydrophobic coating;
[0051] Figure 3 a) is a photo of the self-cleaning test experimental process of Example 3;
[0052] Figure 3 b) is the contact angle test result of each sample in the solvent tolerance test of Example 3;
[0053] Figure 4 a) is a photo of the oil separation experiment process in Example 4;
[0054] Figure 4 b) is the test result of oil-water separation efficiency and flux in Example 4;
[0055] Figure 5 This is the result of the durability test in Example 5. DETAILED DESCRIPTION
[0056] The following is a detailed description of the present invention. The technical features described below are described based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples.
[0057] <Terms and Definitions>
[0058] In the present specification, the terms "alkyl" and "alkylene" include linear, branched or cyclic alkyl or alkylene groups, unless otherwise specifically stated.
[0059] In the present specification, halogen includes fluorine, chlorine, bromine and iodine.
[0060] In the present specification, "O" in the structural formula represents an oxygen atom, "N" represents a nitrogen atom, and "S" represents a sulfur atom.
[0061] In this specification, the term "superhydrophobic" means that the static water contact angle of the described surface is above 150°, wherein the contact angle can be measured using a contact angle tester.
[0062] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints A and B.
[0063] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.
[0064] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0065] In this specification, the use of "optionally" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.
[0066] In this specification, the unit names used are all international standard unit names, and unless otherwise stated, the "%" used indicates weight or mass percentage.
[0067] In this specification, the references to "preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0068] <Polymer>
[0069] One of the objects of the present invention is to provide a polymer, the main chain of which comprises a repeating unit represented by the following formula (1):
[0070]
[0071] In formula (1), "*" represents a connection site with other repeating units or a terminal group, and each group represented by a letter has the meaning given below.
[0072] R1 and R2 are identical or different and represent an alkylene group having 1 to 30 carbon atoms, wherein one or more non-adjacent -CH2- groups are optionally replaced by -O-, -S-, -CO-, -NR- or -CH2- in such a way that the O and / or S atoms are not directly connected to each other. 0 -, -C(=O)NH-, -C(=O)O-, -OC(=O)-, -C=C-, and wherein one or more hydrogen atoms are optionally substituted by halogen.
[0073] Preferably, R1 represents a group -OZO-, wherein Z represents an alkylene group having 1 to 20 carbon atoms, preferably 4 to 18, more preferably 6 to 16 (e.g. 7, 8, 9, 10, 11, 12, 13, 14, 15, etc.), wherein one or more non-adjacent -CH2- groups in the alkylene group are optionally replaced by -O-, -S-, -CO-, -C(=O)O-, -OC(=O)- in a manner that O and / or S atoms are not directly connected to each other, and wherein one or more hydrogen atoms are optionally replaced by halogen. Z preferably represents butylene, pentylene, hexylene, heptylene, octylene, nonylene, decylene, undecylene or dodecylene.
[0074] The chain length of the group represented by R1 affects the thermodynamic properties of polymer.When R1 in group, alkyl chain length is longer (for example, greater than or equal to 6 carbons), polymer chain section is relatively long, and main and side chain groups move more freely, then it is more conducive to hydrophobic groups being arranged in a thermodynamically stable manner (i.e., the manner in which surface energy is the lowest) on material surface.Therefore, from the perspective of being conducive to obtaining super-hydrophobic surface (for example, for use in the super-hydrophobic coating of the present invention), R1 further preferably represents group-OZO-, wherein Z represents hexylene, heptylene, octylene, nonylene, decylene, sub-undecylene or sub-dodecylene.
[0075] Preferably, R2 represents an alkylene group having 2 to 20 carbon atoms, preferably 4 to 18, more preferably 6 to 16 (e.g., 7, 8, 9, 10, 11, 12, 13, 14, 15, etc.), wherein one or more non-adjacent -CH2- groups in the alkylene group are optionally replaced by -O-, -S-, -CO-, -C(=O)O-, -OC(=O)- in a manner that O and / or S atoms are not directly connected to each other, and wherein one or more hydrogen atoms are optionally replaced by halogen. R2 more preferably represents ethylene, propylene, butylene, pentylene, hexylene, heptylene or octylene, which are optionally mono- or poly-substituted by fluorine atoms.
[0076] The chain length of the group represented by R2 and the type and quantity of the substituent, particularly the number of fluorine substituents will affect the thermodynamic properties, hydrophobicity and solubility of polymer. Considering from the angle that is conducive to obtaining super-hydrophobic surface, the more fluorine substituents in the group represented by R2, the longer its carbon chain, the better the hydrophobicity, and the more conducive to the arrangement of hydrophobic groups on the surface of the material, but at the same time its solubility in various solvents will decline, resulting in being difficult to prepare hydrophobic coating by simply dissolving the polymer in an organic solvent. Therefore, in actual use, it is necessary to select the number of suitable chain length and fluorine substituents according to specific needs. Considering from the angle that is more conducive to the super-hydrophobic coating of the present invention, R2 preferably represents ethylene, propylene, butylene, pentylene or hexylene.
[0077] Ar represents a phenylene group, and the phenylene group may be mono- or poly-substituted by an alkyl group having 1 to 10 carbon atoms (preferably 1 to 5, more preferably 1 to 3), an alkoxy group having 1 to 10 carbon atoms (preferably 1 to 5, more preferably 1 to 3), or a halogen group.
[0078] R3 and R4 are the same or different and represent an alkyl group having 5 to 50 carbon atoms, and the alkyl group is optionally substituted with fluorine or multiple substituted groups.
[0079] Preferably, R3 represents an alkyl group having 5 to 20 carbon atoms, preferably 6 to 16 carbon atoms, wherein the alkyl group is polysubstituted with fluorine, more preferably more than 1 / 2 of the hydrogen atoms in the alkyl group are substituted with fluorine, more preferably more than 2 / 3 of the hydrogen atoms are substituted with fluorine.
[0080] Preferably, R4 represents an alkyl group having 12 to 30 carbon atoms, preferably 15 to 25 carbon atoms, and the alkyl group is optionally mono- or poly-substituted by fluorine.
[0081] By making R3 and R4 relatively long alkyl chains, hydrophobicity can be imparted to the polymer, and by making R3 and / or R4 have a fluorine substituent, the hydrophobicity can be further enhanced.
[0082] In a specific embodiment, the polymer of the present invention has a repeating unit represented by formula (1-1):
[0083]
[0084] The groups represented by the individual letters have one of the meanings given above and below.
[0085] In a specific embodiment, the polymer of the present invention has a repeating unit represented by formula (1-2):
[0086]
[0087] The groups represented by the individual letters have one of the meanings given above and below.
[0088] In a specific embodiment, the polymer of the present invention has a repeating unit represented by formula (1-3):
[0089]
[0090] The groups represented by each letter have one of the meanings given above and below, and p and q, the same or different, represent an integer between 2 and 20, preferably 2 to 12, more preferably 2, 3, 4, 5, 6, 7, 8, 9, 10.
[0091] In one embodiment, the number average molecular weight (Mn) of the polymer of the present invention is 2,000 to 100,000, preferably 4,000 to 80,000, more preferably 6,000 to 50,000, further preferably 8,000 to 40,000, even more preferably 10,000 to 30,000.
[0092] In one embodiment, the molecular weight distribution (PDI) of the polymer of the present invention is 1.5 to 3, preferably 1.7 to 2.5, and more preferably 1.8 to 2.3.
[0093] <Polymer Preparation Method>
[0094] An object of the present invention is to provide a method for preparing the polymer of the present invention, which comprises the following steps:
[0095] Step a): reacting the compound represented by formula (2) and the compound represented by formula (3) with thiourea to obtain a monomer B represented by formula (4);
[0096]
[0097] Step b): subjecting the monomer A represented by formula (5) to addition polymerization with the monomer B to obtain a precursor polymer represented by formula (6);
[0098]
[0099] Step c): subjecting the precursor polymer represented by formula (6) to a substitution reaction with the compound represented by formula (7) to obtain the polymer;
[0100] R3-I Formula (7)
[0101] Wherein, each group in formula (2) to formula (7) has one of the definitions given above and below, and n represents the number of repeating units in the precursor polymer, which is an integer of 1 to 50, preferably 2 to 40, more preferably 3 to 25, further preferably 4 to 20, and particularly preferably 5 to 15.
[0102] The various steps of the preparation method of the present invention are described in detail below.
[0103] Step a)
[0104] In step a), a compound containing two terminal aldehyde groups represented by formula (2), a β-ketoester compound represented by formula (3) and thiourea are subjected to a Biginelli reaction to obtain a monomer B containing two terminal DHPMT structures represented by formula (4).
[0105] The Biginelli reaction can be carried out under suitable conditions known in the art.
[0106] In one embodiment, the reaction temperature in step a) is 25 to 150°C, preferably 50 to 130°C, more preferably 80 to 120°C.
[0107] In one embodiment, the reaction time in step a) is 2 to 24 hours, preferably 4 to 12 hours.
[0108] In one embodiment, the reaction of step a) is carried out in the presence of a catalyst, and the catalyst may be one or more selected from Bronsted acid and Lewis acid. Preferably, the catalyst is one or more selected from magnesium chloride, p-toluenesulfonic acid, hydrochloric acid, zinc chloride, cerium ammonium nitrate, ytterbium trifluoromethanesulfonate, and trimethylchlorosilane.
[0109] In one embodiment, the amount of the catalyst used is 10 to 30 mol%, preferably 15 to 25 mol%, based on the compound represented by formula (2).
[0110] In one embodiment, the reaction of step a) is carried out in a solvent, and the solvent is a polar solvent, preferably one or more selected from acetic acid, N,N-dimethylformamide, methanol, ethanol, and acetonitrile.
[0111] In one embodiment, the ratio of the compound represented by formula (2): the compound represented by formula (3): thiourea is 1: (1.8-2.2): (2.5-3.5), preferably 1: (1.9-2.1): (2.8-3.2), based on moles.
[0112] In a particularly preferred embodiment, the β-keto acid ester compound represented by formula (3) is one or more selected from ethyl acetoacetate, propyl acetoacetate, butyl acetoacetate, hexyl acetoacetate, octyl acetoacetate, decyl acetoacetate, dodecyl acetoacetate, tetradecyl acetoacetate, hexadecyl acetoacetate, and octadecyl acetoacetate.
[0113] In one embodiment, after the reaction is completed, the solid product, ie, monomer B, is collected by water precipitation. Specifically, the reaction solution is dropped into cold water for precipitation, and the solvent is washed away.
[0114] Step b)
[0115] In step b), monomer B having two terminal DHPMT structures represented by formula (4) and monomer A having two terminal acrylate structures represented by formula (5) are subjected to addition polymerization to obtain a precursor polymer having a DHPMT structure represented by formula (6).
[0116] In one embodiment, the addition polymerization reaction is carried out in the presence of a catalyst, wherein the catalyst is a base, and the base is preferably an inorganic base, and more preferably one or more selected from sodium carbonate, potassium carbonate, potassium hydroxide, and sodium hydroxide.
[0117] In one embodiment, the addition polymerization reaction is carried out in a solvent, which is a polar aprotic solvent, preferably one or more selected from acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, more preferably N,N-dimethylformamide.
[0118] In one embodiment, based on moles, monomer A:monomer B=1:(0.9-1.1), preferably 1:(0.95-1.05).
[0119] In one embodiment, based on moles, monomer A:monomer B:catalyst=1:(0.9-1.1):(0.05-0.20), preferably 1:(0.95-1.05):(0.08-0.15).
[0120] In one embodiment, the reaction temperature is 80 to 120°C, preferably 90 to 110°C.
[0121] In one embodiment, the reaction time is 4 to 12 hours.
[0122] In a particularly preferred embodiment, the monomer A containing two terminal acrylate structures shown in formula (5) is a diol diacrylate, specifically one or more selected from 1,2-ethylene glycol diacrylate, 1,3-propylene glycol diacrylate, 1,4-butylene glycol diacrylate, 1,6-hexanediol diacrylate, 2,2,3,3,4,4-hexafluoro-1,6-hexanediol diacrylate, among which 1,6-hexanediol diacrylate is particularly preferred.
[0123] In one embodiment, the polymerization process is tracked. Specifically, the molecular weight of the polymer in the polymerization system is detected at certain time intervals (e.g., 30 min, 60 min, 90 min, 120 min) (e.g., using gel permeation chromatography (GPC)), and the reaction is stopped when the molecular weight of the polymer in the polymerization system stops increasing.
[0124] In one embodiment, step b) further comprises post-treating the polymer product (ie, the precursor polymer). For example, the polymer product can be separated and purified by precipitation with a poor solvent (eg, water, ether) or by dialysis.
[0125] Preferably, the post-treatment is carried out by a poor solvent precipitation method, wherein the poor solvent used is preferably diethyl ether. Specifically, the reaction solution is poured into diethyl ether, the precipitate is filtered and optionally washed with water and / or diethyl ether, and then optionally dried.
[0126] Step c)
[0127] In step c), the precursor polymer represented by formula (6) is subjected to a substitution reaction with the halogenated compound represented by formula (7) to introduce a long alkyl side chain into the side chain of the precursor polymer.
[0128] In one embodiment, the substitution reaction in step c) is carried out in the presence of a base and an iodine salt. The base is preferably an inorganic base, more preferably potassium carbonate and / or sodium carbonate. The iodine salt is preferably sodium iodide and / or potassium iodide.
[0129] In one embodiment, the substitution reaction of step c) is carried out in a solvent, which is a polar aprotic solvent, preferably one or more selected from acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, more preferably N,N-dimethylformamide.
[0130] In a specific embodiment, on a molar basis, the precursor polymer: the compound represented by formula (7): the base: the iodine salt = 1: (3.5-4.5): (2.5-4.5): (0.05-0.5), preferably 1: (3.8-4.2): (2.8-4.0): (0.1-0.3), for example 1: 4: 3: 0.2.
[0131] In one embodiment, the reaction temperature is 80 to 120°C, preferably 90 to 110°C.
[0132] In one embodiment, the reaction time is 12 to 36 hours, preferably 18 to 30 hours.
[0133] In a particularly preferred embodiment, the halogenated compound represented by formula (7) is a halogenated alkane, specifically an iodinated alkane, more specifically a perfluoroalkyl-substituted iodoethane, for example, one or more selected from 2-(perfluorooctyl) iodoethane, 2-(perfluorohexyl) iodoethane, and 2-(perfluorobutyl) iodoethane.
[0134] In one embodiment, the process of the substitution reaction is tracked and monitored. Specifically, nuclear magnetic resonance hydrogen spectroscopy ( 1 H NMR) to monitor the degree of substitution reaction, and the reaction can be stopped at an appropriate degree of substitution according to the specific requirements for the hydrophobic properties of the polymer.
[0135] In one embodiment, the product can be isolated and purified by dialysis or ether precipitation. Preferably, the dialysis method is used. Specifically, the reaction solution can be filtered and the filtrate can be dialyzed and purified in a methanol solution using a dialysis bag with a molecular weight cutoff of 3500 Da.
[0136] Additional Steps
[0137] Step a')
[0138] In one embodiment, the preparation method of the present invention further comprises step a' of preparing the compound represented by formula (2). The specific preparation method of the compound represented by formula (2) may be a preparation method known in the art.
[0139] For example, in the embodiment where R1 represents a group -OZO-, the compound represented by formula (2) can be prepared by the following method:
[0140] The compound represented by formula (8) is reacted with the compound represented by formula (9) to obtain a compound represented by formula (2') having two terminal aldehyde groups:
[0141]
[0142] Therein, X is halogen, preferably Br; Ar and Z have one of the meanings given above and below.
[0143] In one embodiment, the reaction is carried out under base catalysis, and the base is preferably an inorganic base, which can be one or more selected from potassium carbonate, sodium carbonate, potassium hydroxide, and sodium hydroxide.
[0144] In one embodiment, the reaction is carried out in a solvent, which may be a polar aprotic solvent, for example, one or more selected from acetonitrile, dioxane, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0145] In one embodiment, on a molar basis, the compound represented by formula (8): the compound represented by formula (9): the base = (1.7-2.5):1:(2.5-3.5), preferably (2-2.2):1:(2.8-3.2), for example 2.1:1:3.
[0146] In one embodiment, the reaction temperature is 80°C to 120°C, preferably 90°C to 110°C.
[0147] In one embodiment, the reaction time is 6 to 24 hours, preferably 12 to 18 hours.
[0148] In one embodiment, after the reaction is completed, the solid product, ie, the compound represented by formula (2'), can be collected by precipitation with an aqueous alkali solution.
[0149] In a particularly preferred embodiment, the compound represented by formula (8) is p-hydroxybenzaldehyde, and the dihalogenated compound represented by formula (9) is one or more selected from 1,4-dibromobutane, 1,6-dibromohexane, and 1,8-dibromooctane.
[0150] Step a)
[0151] In one embodiment, the preparation method of the present invention further comprises the step of preparing the β-ketoester compound represented by formula (3).
[0152] In one embodiment, the compound represented by formula (3) can also be prepared by the following method:
[0153] Tert-butyl acetoacetate is reacted with an alcohol represented by formula (10):
[0154] R4-OH formula (10)
[0155] In one embodiment, the reaction is carried out in a solvent, which can be an aprotic solvent, preferably an aprotic solvent with a high boiling point (boiling point above 100° C.), for example, one or more selected from toluene, xylene, dimethyl sulfoxide, pyridine, N-methylpyrrolidone, diphenyl ether, and dodecane, preferably selected from toluene and xylene.
[0156] In one embodiment, the ratio of tert-butyl acetoacetate to the alcohol of formula (10) is 1:(1-1.5), preferably 1:(1.1-1.3), for example 1:1.2, based on moles.
[0157] In one embodiment, the reaction temperature is 90-120°C.
[0158] In one embodiment, the reaction time is 6 to 20 hours.
[0159] <Superhydrophobic paints and coatings>
[0160] An object of the present invention is to provide a super hydrophobic coating comprising the polymer of the present invention and a solvent.
[0161] In one embodiment, the content of the polymer of the present invention in the super hydrophobic coating is 0.001 to 1 mol / L, preferably 0.005 to 0.1 mol / L, more preferably 0.008 to 0.05 mol / L, for example 0.01 mol / L, calculated as repeating units.
[0162] In one embodiment, the content of the polymer of the present invention in the super hydrophobic coating is 1 to 30 wt %, preferably 2 to 20 wt %, more preferably 3 to 15 wt %, and further preferably 5 to 10 wt %.
[0163] The present invention has no particular limitation on the solvent, which may be any suitable solvent known in the coating field, including water and organic solvents.
[0164] In one embodiment, the solvent is selected from one or more of hydrocarbons, chlorinated hydrocarbons, esters, ethers, ketones, nitriles, sulfoxides and amide solvents. Specifically, the solvent can be selected from ethyl acetate, butyl acetate, propylene glycol methyl ether, propylene glycol methyl ether acetate, propylene glycol butyl ether, ethylene glycol methyl ether, ethylene glycol butyl ether, methanol, ethanol, propanol, isopropanol, n-butanol, isobutanol, acetone, methyl ethyl ketone, cyclohexanone, methyl isobutyl ketone, methyl n-butyl ketone, methyl amyl ketone, 3-pentanone, dioxane, dichloromethane, acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone. From the perspective of easy removal of solvent to form a coating, a low boiling point solvent is preferred, such as a solvent with a boiling point of less than 100°C. From the viewpoint of facilitating the dispersion and solubility of the polymer, halogenated hydrocarbons, tetrahydrofuran, amides (eg, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, etc.), and dimethyl sulfoxide are preferred.
[0165] In the super hydrophobic coating of the present invention, the content of the solvent may be 70 to 99 wt %, preferably 80 to 98 wt %, more preferably 85 to 97 wt %, and further preferably 90 to 95 wt %.
[0166] In one embodiment, the super hydrophobic coating of the present invention further comprises other polymers or polymer precursors.Other polymers can be base polymers known in the field of coatings, including but not limited to (meth) acrylic polymers, epoxies, polyesters, polyurethanes, etc.Polymer precursors refer to substances that can form a part of a polymer molecular chain during coating curing, such as monomers forming the above-mentioned various polymers.
[0167] In one embodiment, the super-hydrophobic coating of the present invention may further optionally include an additive, which may be any suitable additive known in the coating field, and those skilled in the art may select the additive according to specific needs.
[0168] In a specific embodiment, the additive is one or more selected from pigments, dyes, nanoparticles, leveling aids, dispersing aids, and wetting aids.
[0169] The content of the additive in the super hydrophobic coating may be 0 to 30 wt %, such as 1 to 25 wt %, and another example is 2 to 20 wt %.
[0170] An object of the present invention is to provide a super hydrophobic coating comprising the polymer of the present invention. In one embodiment, other polymers and / or additives as described above are optionally included.
[0171] In one embodiment, the content of the polymer of the present invention in the super hydrophobic coating is 10wt% or more, preferably 30wt% or more, more preferably 50wt% or more, further preferably 70wt%, and even more preferably 90wt% or more. There is no particular restriction on the upper limit of the content of the polymer of the present invention in the super hydrophobic coating, which may be 100wt%, or less than 95wt%, or less than 85wt%, or less than 75wt%.
[0172] In one embodiment, the super hydrophobic coating of the present invention is formed by curing the super hydrophobic coating of the present invention. Therefore, the super hydrophobic coating of the present invention may also include other non-volatile components (other polymers, additives) in the super hydrophobic coating described above.
[0173] <Super hydrophobic copper mesh and preparation method thereof>
[0174] An object of the present invention is to provide a super-hydrophobic copper mesh, which comprises a copper mesh substrate and a polymer layer located on the surface of the copper mesh substrate, wherein the polymer layer comprises the polymer of the present invention.
[0175] In one embodiment, the polymer layer consists of a polymer according to the invention.
[0176] In the polymer of the present invention, sulfur in the DHPMT derivative structure can coordinate with divalent copper, so that in the super-hydrophobic copper mesh of the present invention, the polymer layer is firmly combined with the copper oxide mesh substrate and is not easy to fall off, thereby having excellent durability and solvent tolerance.
[0177] The present invention has no particular limitation on the copper mesh substrate, which may have any shape and size, and those skilled in the art may select the shape and size according to specific needs.
[0178] In one embodiment, the mesh size of the copper mesh substrate is 10 to 500 μm.
[0179] In one embodiment, the copper mesh substrate is in the shape of a circle, rectangle, square, triangle, trapezoid or polygon. For the above shapes, the longest diameter in the area can be more than 1 cm, more than 10 cm or more than 1 m, or less than 100 m, less than 10 m or less than 5 m.
[0180] In one embodiment, the thickness of the polymer layer is between 50 nm and 50 μm.
[0181] In one embodiment, the water contact angle of the superhydrophobic copper mesh is 150° or more, such as 151° or more, 152° or more, 153° or more, or 154° or more.
[0182] An object of the present invention is to provide a method for preparing a super hydrophobic copper mesh of the present invention, which comprises the following steps:
[0183] The super hydrophobic coating of the present invention is applied to the surface of a copper mesh substrate and optionally dried.
[0184] Coating can be carried out by any suitable method known in the art, including but not limited to spin coating, brush coating, dip coating, roller coating, spray coating, etc. From the perspective of being conducive to the formation of the polymer layer, dip coating is preferably used. Specifically, coating can be carried out by immersing the copper mesh substrate in the super hydrophobic coating of the present invention and then taking it out.
[0185] In one embodiment, after coating, the coated copper mesh substrate is dried. Drying can be performed by any suitable method known in the art, including but not limited to natural air drying (20-30° C.), drying (40-80° C.), baking, hot air drying, etc.
[0186] In one embodiment, the method for preparing the super-hydrophobic copper mesh of the present invention further comprises the step of pre-treating the copper mesh substrate. Specifically, an alkaline oxidizing corrosion solution can be used for treatment to remove oxides on the surface of the copper mesh substrate. More specifically, the copper mesh substrate can be immersed in the alkaline oxidizing corrosion solution, and the immersion time is preferably 1 to 30 minutes.
[0187] In one embodiment, the alkaline oxidizing etching solution can be a mixed aqueous solution of an alkali (e.g., sodium hydroxide, potassium hydroxide) and an oxidizing substance. The oxidizing substance can be a peroxide (e.g., hydrogen peroxide) and / or a persulfate (e.g., potassium persulfate, sodium persulfate). The concentration of the alkali can be 0.5-1.5 mol / L, and the concentration of the oxidizing substance can be 0.05-0.15 mol / L.
[0188] <Oil-Water Separation>
[0189] The present invention also correspondingly relates to the use of the super-hydrophobic copper mesh of the present invention for oil-water separation.
[0190] The present invention also correspondingly relates to an oil-water separation method, which comprises the following steps: filtering the oil-water mixture using the super-hydrophobic copper mesh of the present invention.
[0191] Due to the super-hydrophobicity of the super-hydrophobic copper mesh of the present invention, during the filtering process, water in the oil-water mixture will be retained, while the oil can smoothly pass through the copper mesh, thereby achieving oil-water separation.
[0192] Example
[0193] The present invention is further described by enumerating specific implementation cases below. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content recorded in the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the present invention equally.
[0194] Example 1: Preparation of polymer P2
[0195] The synthetic route of polymer P2 is as follows Figure 1 As shown in a).
[0196] 1. Preparation of Precursor Polymer P1
[0197] In the first step, p-hydroxybenzaldehyde, 1,6-dibromohexane and potassium carbonate were added to dioxane in a molar ratio of 2.1:1:3, wherein the concentration of dibromohexane was 1 mol / L, and the temperature was raised to 100°C and refluxed for 12 hours. After the reaction was completed, the reaction solution was dropped into cold water for precipitation and washed with petroleum ether to obtain a precursor diCHO containing two terminal aldehyde groups, which was a yellow solid powder with a yield of about 90%.
[0198] In the second step, tert-butyl acetoacetate and octadecyl alcohol are dissolved in toluene at a molar ratio of 1:1.2, wherein the concentration of tert-butyl acetoacetate is 1 mol / L, and the temperature is raised to 110° C. and refluxed for 12 hours. After the reaction is completed, the reaction solvent is removed by rotary evaporation, and flash column chromatography is performed with petroleum ether as an eluent to obtain octadecyl acetoacetate as a white solid powder with a yield of about 95%.
[0199] In the third step, diCHO, octadecyl acetoacetate and thiourea are dissolved in acetic acid at a molar ratio of 1:2:3, wherein the concentration of diCHO is about 2 mol / L, and 10 mol% of magnesium chloride relative to diCHO is added as a catalyst, and the temperature is raised to 100°C for reaction for 6 hours. After the reaction is completed, the reaction solution is dropped into cold water for precipitation, and the acetic acid is washed off with a sodium bicarbonate solution to obtain the B2 monomer as a yellow solid powder with a yield of about 80%.
[0200] The commercial monomer 1,6-hexanediol diacrylate was purified by a silica gel column (the eluent was petroleum ether: ethyl acetate = 20:1) to obtain the purified A2 monomer. The purified A2 monomer and B2 monomer were dissolved in N,N-dimethylformamide at a molar ratio of 1:1. The concentration of both monomers was 1 mol / L. After the system was heated to 100°C, 10 mol% of potassium carbonate relative to the A2 monomer was added as a polymerization catalyst. The polymerization process was monitored by gel permeation chromatography. When the molecular weight of the system stopped increasing (generally after 4 hours of polymerization), the reaction solution was precipitated in cold ether and washed with cold water and cold ether to obtain the precursor polymer P1, which was a yellow-brown solid.
[0201] Depend on Figure 1 b) shown in 1 The H NMR spectrum shows that the precursor polymer P1 with clear structural characterization was successfully obtained. Its Mn was measured by GPC and was 7.0×10 3 g / mol, PDI=2.1.
[0202] 2. Preparation of polymer P2
[0203] Precursor polymer P1 (in terms of repeating units), 2-perfluorooctyl iodoethane, potassium carbonate and sodium iodide were added to N,N-dimethylformamide at a molar ratio of 1:4:3:0.2, wherein the concentration of precursor polymer P1 was 1 mol / L (in terms of repeating units), and the temperature was raised to 100°C for reaction for 18 hours. The inorganic salts in the reaction solution were filtered and purified by dialysis (dialysis solution methanol, molecular weight cutoff 3500Da) to obtain polymer P2.
[0204] Depend on Figure 1 c) shown 1 The H NMR spectrum shows that the target polymer P2 was successfully synthesized, and its Mn was measured by GPC to be 9.9×10 3 g / mol, PDI=2.0.
[0205] Example 2: Preparation of super hydrophobic copper mesh
[0206] Prepare a mixed aqueous solution of 1 mol / L sodium hydroxide and 0.1 mol / L potassium persulfate as an alkaline oxidizing corrosion solution. Cut a 400-mesh commercial phosphor copper mesh into a size of 4 cm × 4 cm and ultrasonically clean it with 75% ethanol. Soak the cleaned copper mesh in the corrosion solution for 10 minutes, take it out and wash the surface with deionized water and dry it. The polymer P2 obtained in Example 1 is dissolved in dichloromethane at a concentration of 0.01 mol / L (in terms of repeating units) to prepare a super-hydrophobic coating. Then dip the above-dried copper mesh in the obtained super-hydrophobic coating, take it out and directly place it in a 50°C oven to dry, and a super-hydrophobic copper mesh is obtained.
[0207] The copper mesh before and after surface modification with superhydrophobic coating was characterized using a contact angle tester and a scanning electron microscope.
[0208] Depend on Figure 2 From the contact angle test results of a), it can be seen that the water contact angle of the copper mesh before modification is 0°, showing super hydrophilicity, while after the surface is modified with a super hydrophobic coating, the water contact angle is 150.8°, showing super hydrophobicity.
[0209] Depend on Figure 2 From the scanning electron microscope image shown in b), it can be seen that there are some more particles and mucous membrane-like substances on the copper substrate after modification, which indicates that the polymer P2 is successfully modified onto the copper grid by dip coating.
[0210] Example 3: Self-cleaning properties of superhydrophobic copper mesh and characterization of its stability in different liquid environments
[0211] 3-1: Self-cleaning test experiment
[0212] The super-hydrophobic copper mesh prepared in Example 2 was cut into a size of 2 cm × 4 cm and flatly attached to the surface of a glass slide. An appropriate amount of copper powder was sprinkled on the surface to simulate solid contaminants in the copper mesh during use. It was rinsed with deionized water to simulate the scouring process of rainwater. The residual copper powder after washing was observed to evaluate the self-cleaning property of the super-hydrophobic copper mesh. Photos of the experimental process are shown in the figure. Figure 3 As shown in a).
[0213] Depend on Figure 3 As shown in a), the copper powder on the super-hydrophobic copper mesh can be cleaned by simple washing, and its surface is clean again, which indicates that the super-hydrophobic copper mesh has self-cleaning properties.
[0214] 3-2: Solvent resistance test
[0215] The super-hydrophobic copper mesh prepared in Example 2 was cut into thin strips of comparable size (about 1 cm × 4 cm) and immersed in different liquid environments, including three aqueous solutions with different pH values (hydrochloric acid with pH = 1, sodium chloride solution with pH = 7 and a mass fraction of 3%, and sodium hydroxide solution with pH = 13) and four different organic solvents (petroleum ether PE, dichloromethane DCM, tetrahydrofuran THF, and ethanol EtOH). In the experiment using an aqueous solution, the super-hydrophobic copper mesh was immersed in an aqueous solution environment for 48 hours. In the experiment using an organic solvent, the super-hydrophobic copper mesh was immersed in an organic solvent and treated with ultrasound for 15 minutes. After immersion, the super-hydrophobic copper mesh was taken out and dried, and the water contact angle on its surface was measured again to evaluate the stability of the super-hydrophobic property of the super-hydrophobic copper mesh in different liquid environments. The contact angle test results are shown in FIG. Figure 3 As shown in b).
[0216] Depend on Figure 3 From the contact angle data of b), it can be seen that the superhydrophobic copper mesh still has good hydrophobicity after being immersed in different liquid environments, indicating that the superhydrophobic copper mesh has good solvent tolerance and environmental stability.
[0217] Example 4: Oil-water separation performance test of super-hydrophobic copper mesh
[0218] according to Figure 4 As shown in a), the super-hydrophobic copper mesh obtained in Example 2 is fixed between two glass tubes with a polytetrafluoroethylene fixture, and the outlet of the lower tube is received by a beaker as an oil-water separation device. The organic solvent dichloromethane DCM is mixed with water in equal volumes to serve as a model oil-water mixture. For ease of observation, Oil Red O is also added as a dye to dye the oil layer so that its interface with the water layer is clearer.
[0219] 20 mL of the model oil-water mixture was poured into the oil-water separation device, and the flux of the superhydrophobic copper mesh in separating the oil-water mixture was evaluated by measuring the time for all the oil in the mixture to pass through the superhydrophobic copper mesh; the efficiency of the superhydrophobic copper mesh in oil-water separation was evaluated by measuring the water content in the liquid passing through the superhydrophobic copper mesh using a Karl-Fischer trace water tester.
[0220] The other three organic solvents, petroleum ether PE, toluene, and cyclohexane CYH, were mixed with water in equal volumes as model oil-water mixtures and tested for oil-water separation performance in the same manner as above.
[0221] The oil-water separation performance test results of the super-hydrophobic copper mesh obtained in Example 2 for four model oil-water mixtures are as follows: Figure 4 As shown in b).
[0222] pass Figure 4 b) It can be seen that for the four model oil-water mixtures, the superhydrophobic copper mesh of the present invention shows a large separation flux and a high separation efficiency, which indicates that the superhydrophobic copper mesh of the present invention can be used for oil-water separation and has a satisfactory separation flux and separation efficiency.
[0223] Example 5: Durability test of super hydrophobic copper mesh
[0224] Using the oil-water separation device in Example 4, a dichloromethane / water mixture was used as a model oil-water mixture, and 10 consecutive oil-water separation experiments were performed on the same super-hydrophobic copper mesh sample. The flux and efficiency of each separation were evaluated according to the method in Example 4. The results are shown in FIG. Figure 5 shown.
[0225] pass Figure 5It can be seen that when the super-hydrophobic copper mesh of the present invention is continuously subjected to multiple oil-water separations, the separation efficiency and separation flux can be maintained at a relatively high level, which indicates that the super-hydrophobic copper mesh of the present invention has good durability.
[0226] Industrial Applicability
[0227] The polymer and super-hydrophobic coating of the present invention can be widely used in preparing super-hydrophobic coatings, and have broad application prospects in the field of oil-water separation.
Claims
1. A polymer, characterized in that It contains the repeating unit represented by the following formula (1): in, R1 and R2 are identical or different and represent an alkylene group having 1 to 30 carbon atoms, wherein one or more non-adjacent -CH2- groups are optionally replaced by -O-, -S-, -CO-, -NR- or -CH2- in such a way that the O and / or S atoms are not directly connected to each other. 0 -, -C(=O)NH-, -C(=O)O-, -OC(=O)-, -C=C-, and wherein one or more hydrogen atoms are optionally substituted by halogen; Ar represents a phenylene group, which is optionally substituted mono- or poly-substituted by an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, or a halogen group; R3 and R4 are the same or different and represent an alkyl group having 5 to 50 carbon atoms, wherein the alkyl group is optionally substituted with fluorine or polysubstituted with fluorine; * indicates the attachment site.
2. The polymer according to claim 1, characterized in that In formula (1), R1 represents a group -OZO-, wherein Z represents an alkylene group having 1 to 20 carbon atoms, and one or more non-adjacent -CH2- groups in the alkylene group are optionally replaced by -O-, -S-, -CO-, -C(=O)O-, -OC(=O)- in a manner that O and / or S atoms are not directly connected to each other, and one or more hydrogen atoms are optionally substituted by halogen; R2 represents an alkylene group having 2 to 20 carbon atoms, and one or more non-adjacent -CH2- groups in the alkylene group are optionally replaced by O and / or S atoms. Or the S atoms are not directly connected to each other and are replaced by -O-, -S-, -CO-, -C(=O)O-, -OC(=O)-, and one or more hydrogen atoms are optionally substituted by halogen; Ar represents a phenylene group, and the phenylene group is optionally substituted by an alkyl group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, or a halogen; R3 represents an alkyl group having 5 to 20 carbon atoms, and the alkyl group is optionally substituted by fluorine; R4 represents an alkyl group having 12 to 30 carbon atoms, and the alkyl group is optionally substituted by fluorine.
3. The polymer according to claim 2, characterized in that Wherein Z represents an alkylene group having 4 to 12 carbon atoms; R2 represents an alkylene group having 4 to 12 carbon atoms; Ar represents a phenylene group, which is optionally mono- or poly-substituted by an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, or a halogen group; R3 represents an alkyl group having 6 to 16 carbon atoms, which is optionally mono- or poly-substituted by fluorine; R4 represents an alkyl group having 15 to 25 carbon atoms, which is optionally mono- or poly-substituted by fluorine.
4. The method for preparing a polymer according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step a): reacting the compound represented by formula (2) and the compound represented by formula (3) with thiourea to obtain a monomer B represented by formula (4); Step b): subjecting the monomer A represented by formula (5) to addition polymerization with the monomer B to obtain a precursor polymer represented by formula (6); Step c): subjecting the precursor polymer represented by formula (6) to a substitution reaction with the compound represented by formula (7) to obtain the polymer; R3-I Formula (7) Wherein, each group in formula (2) to formula (7) has the definition given in any one of claims 1 to 3; n represents the number of repeating units in the precursor polymer, which is an integer of 1 to 50.
5. The preparation method according to claim 4, characterized in that: The reaction in step a) is carried out in a solvent in the presence of a catalyst, wherein the catalyst is one or more selected from Bronsted acid and Lewis acid, preferably one or more selected from magnesium chloride, p-toluenesulfonic acid, hydrochloric acid, zinc chloride, ammonium cerium nitrate, ytterbium trifluoromethanesulfonate, and trimethylsilyl chloride; the solvent is a polar solvent, preferably one or more selected from acetic acid, N,N-dimethylformamide, methanol, ethanol, and acetonitrile; in terms of moles, the compound represented by formula (2): the compound represented by formula (3): thiourea = 1: (1.8-2.2): (2.5-3.5); the reaction temperature is 25-100°C; the reaction time is 2-24 hours; The addition polymerization reaction in step b) is carried out in a solvent in the presence of a catalyst, wherein the catalyst is a base, and the base is preferably an inorganic base, and more preferably one or more selected from sodium carbonate, potassium carbonate, potassium hydroxide, and sodium hydroxide; the solvent is a polar aprotic solvent; in terms of moles, monomer A:monomer B:catalyst=1:(0.9-1.1):(0.05-0.20); the reaction temperature is 80-120°C; and the reaction time is 4-12 hours; The substitution reaction in step c) is carried out under the catalysis of a base and an iodine salt, wherein the base is preferably an inorganic base, more preferably potassium carbonate and / or sodium carbonate; the iodine salt is preferably sodium iodide and / or potassium iodide; in terms of moles, the precursor polymer: the compound represented by formula (7): the base: the iodine salt = 1: (3.5-4.5): (2.5-4.5): (0.05-0.5); the reaction temperature is 80-120° C.; and the reaction time is 12-36 hours.
6. A super hydrophobic coating, characterized in that: The method comprises the polymer according to any one of claims 1 to 3 and a solvent.
7. A super hydrophobic coating, characterized in that: The method comprises the polymer according to any one of claims 1 to 3.
8. A super hydrophobic copper mesh, characterized in that: The invention comprises a copper mesh substrate and a polymer layer located on the surface of the copper mesh substrate, wherein the polymer layer comprises the polymer according to any one of claims 1 to 3.
9. The method for preparing a super-hydrophobic copper mesh according to any one of claim 8, wherein The following steps are involved: The super-hydrophobic coating according to claim 6 is applied to the surface of the copper mesh substrate and optionally dried.
10. Use of the super-hydrophobic copper mesh according to claim 8 for oil-water separation.
Citation Information
Patent Citations
High-weather-resistance super-hydrophobic polymer as well as preparation method and application thereof
CN116217935A
Rust-preventive agent and surface-treated metal material
JP2010144205A